Field-driven chiral bubble dynamics analysed by a semi-analytical approach. (20th November 2017) - Vandermeulen, J; Leliaert, J; Dupré, L; Van Waeyenberge, B
Abstract: Nowadays, field-driven chiral bubble dynamics in the presence of the Dzyaloshinskii–Moriya interaction are a topic of thorough investigation. In this paper, a semi-analytical approach is used to derive equations of motion that express the bubble wall (BW) velocity and the change in in-plane magnetization angle as function of the micromagnetic parameters of the involved interactions, thereby taking into account the two-dimensional nature of the bubble wall. It is demonstrated that the equations of motion enable an accurate description of the expanding and shrinking convex bubble dynamics and an expression for the transition field between shrinkage and expansion is derived. In addition, these equations of motion show that the BW velocity is not only dependent on the driving force, but also on the BW curvature. The absolute BW velocity increases for both a shrinking and an expanding bubble, but for different reasons: for expanding bubbles, it is due to the increasing importance of the driving force, while for shrinking bubbles, it is due to the increasing importance of contributions related to the BW curvature. Finally, using this approach we show how the recently proposed magnetic bubblecade memory can operate in the flow regime in the presence of a tilted sinusoidal magnetic field and at greatly reduced bubble sizes compared to the original device prototype.